Association study of Disrupted-In-Schizophrenia-1 gene variants and tardive dyskinesia. (1st November 2018) - Lu, Justin Y.; Tiwari, Arun K.; Zai, Gwyneth C.; Rastogi, Anjali; Shaikh, Sajid A.; Müller, Daniel J.; Voineskos, Aristotle N.; Potkin, Steven G.; Lieberman, Jeffrey A.; Meltzer, Herbert Y.; Remington, Gary; Wong, Albert H.C.; et al.
Highlights: Nine single-nucleotide polymorphisms (SNPs) in the Disrupted in Schizophrenia 1 ( DISC1 ) gene was investigated for possible association with TD. The tested DISC1 SNPs were not significant associated with TD. The DISC1 rs11122359 may be interacting with the vesicular monoamine transporter 2 (VMAT2/ SLC18A2 ) rs363224 in TD. Abstract: Tardive dyskinesia (TD) is an involuntary movement disorder that occurs in ∼20% of patients after extended antipsychotic use. Its pathophysiology is unclear; however, familial patterns and gene association studies indicate an inherited component to risk. The disrupted in schizophrenia 1 ( DISC1 ) gene was selected for analysis because it interacts with and regulates two important proteins involved in antipsychotic medication action: the dopamine D2 receptor and the cAMP phosphodiesterase type IVB (PDE4B). The D2 receptor is the obligate target of all existing antipsychotic medications, and PDE4B hydrolyzes cAMP, a core signaling molecule activated by agonist binding to the D2 receptor. Notably, PDE4B inhibitors such as rolipram have been shown to reduce TD-like behaviours in animal models. Nine single-nucleotide polymorphisms (SNPs) in the DISC1 gene were investigated in a sample of 193 chronic schizophrenia patients for association with the presence and severity of TD, with age and sex as additional variables. TD severity was measured using the Abnormal Involuntary Movement Scale (AIMS). Two DISC1 SNPs were associated with TD severity (uncorrected p < 0.05), but these findings did not survive correction for multiple testing. This preliminary investigation suggests that DISC1 gene variants do not affect risk for TD or severity.